GROW MOVEMENT GAME IN SUN EXPOSURE TO INCREASE CHILDREN'S GROUND-LEVEL MOTOR SKILLS - Munasri, Munasri; Sukiman, Sukiman (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
This research aimed to determine if children aged 5-6 at Setyara Wardani Kindergarten in the Jatiasih District of Bekasi City, West Java, improved their gross motor skills after participating in rough movement games while outside in the sun. This study takes a quantitative approach, adopting an experimental methodology and employing a one-group pre- and post-test design for its experimentation. Twenty-eight children from TK Setyara Wardani's group B4 served as participants. This investigation employed a Likert-scale rubric for data gathering using tests and observation sheets. Descriptive statistics and the paired-samples t-test are employed to evaluate hypotheses and draw conclusions from the data. The above table from the Paired Samples Test shows that when the sig. (2-tailed) is 0.000 0.05, H0 is rejected, whereas H1 is accepted. As a result, we can infer that children's gross motor abilities generally improve during the pre- and post-test periods, suggesting that they gain strength and coordination while engaging in roughhousing in the open air.